2015
DOI: 10.18311/jnr/2015/466
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antibacterial Activity of <i>Manilkara hexandra</i> (Sapotaceae) Seed Extracts and Violacein against Multidrug Resistant <i>Streptococcus mutans

Abstract: Ipomoea reniformis Chaos is claimed in Indian traditional medical practice to be useful in the treatment of epilepsy and neurological disorders. In the present study, pretreatment effect of methanolic extract of Ipomoea reniformis on epilepsy and psychosis was evaluated in rodents using standard procedures. Besides evaluating epileptic and behavioral parameters, neurotransmitters such as Gamma-Amino Butyric Acid (GABA) in epilepsy and in psychosis dopamine, noradrenaline and serotonin contents in the rodent br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Study conducted by Mahida et al showed methanol extract of M. hexandra effectively inhibited the growth of multidrug resistant Staphylococcus aureus and S. epidermidis [26] . The different studies revealed that acetone seed extract, methanolic extract of leaves, roots, aqueous extracts of leaves, aerial parts of M. hexandra, were found to be having good antimicrobial activity [27][28][29][30][31] . Antifungal activity of some plant extracts was tested against the Solanum melongena damping off pathogen, Pythium aphanidermatum in PDA cultures.…”
Section: Microbiological Activitymentioning
confidence: 99%
“…Study conducted by Mahida et al showed methanol extract of M. hexandra effectively inhibited the growth of multidrug resistant Staphylococcus aureus and S. epidermidis [26] . The different studies revealed that acetone seed extract, methanolic extract of leaves, roots, aqueous extracts of leaves, aerial parts of M. hexandra, were found to be having good antimicrobial activity [27][28][29][30][31] . Antifungal activity of some plant extracts was tested against the Solanum melongena damping off pathogen, Pythium aphanidermatum in PDA cultures.…”
Section: Microbiological Activitymentioning
confidence: 99%